Plants vs. zombies. 8, Lawn of doom part 3 - Tobin, Paul, 1965- (Spotlight ; Dark Horse Books, 2020)
Dr. Zomboss loses the contest but has one more trick up his sleeve. Just when all hope seems lost, Crazy Dave finally reveals the results of his experiments with turtles and saves the day.